TRANSFORMING GROWTH FACTOR 1 AT LIVER TRANSPLANTATION - R. M. Kurabekova; O. P. Shevchenko; O. M. Tsiroulnikova (Вестник трансплантологии и искусственных органов, 2015)
This review summarizes the current literature devoted to the analysis of the role of transforming growth factor beta 1 (TGF-β1) at liver transplantation. TGF-β1 plays a key role in the development of liver fi brosis, as well as in development of the immune response; its concentration in the blood and tissue changes in liver diseases. TGF-β1 levels in the blood of the recipients are associated with the development of liver fi brosis, the formation of immune tolerance and immune response to active infection. Measuring the level of TGF-β1 at liver transplantation may have diagnostic and prognostic value for assessing the graft condition. Currently, clinical data on the role of the cytokine at liver transplantation are not accumulated enough and further research on the relation of TGF-β1 levels with different clinical and laboratory parameters in liver transplant patients is needed. The review analyzed 54 sources of literature, more than half of which were published in the last fi ve years.